The production of managerial knowledge and organizational theory : new approaches to writing, producing and consuming theory - Zilber, Tammar B.; Amis, John M.; Mair, Johanna, 1967- (Research in the sociology of organizations, 2019)
This book applies a reflective and critical gaze on the production of knowledge within management and organization studies. Seasoned scholars reflect on how we carry out research to provide insights into the assumptions and practices we employ, and how they affect the production and consumption of managerial knowledge and organization theory.